Empowering Forms. Hegel’s conception of ‘form’ and ‘formal’ - Ficara, Elena (Hegel, Logic and Speculation)

Hegel and Priest on Revising Logic - Ficara, Elena (Graham Priest on Paraconsistency and Dialetheism)

Hegel on the Naturalness of Logic - Ficara, Elena (Argumenta)

Finite-control-set model predictive control for a permanent magnet synchronous motor application with online least squares system identification - Hanke, Sören; Peitz, Sebastian; Wallscheid, Oliver; Böcker, Joachim; Dellnitz, Michael (2019 IEEE International Symposium on Predictive Control of Electrical Drives and Power Electronics (PRECEDE))

Stator flux-based field-oriented position-sensorless control of permanent magnet synchronous motors with limited parameter knowledge - Wallscheid, Oliver; Shafiq, Muhammad Saad; Böcker, Joachim (2019 IEEE 28th International Symposium on Industrial Electronics (ISIE))

Hierarchical model predictive speed and current control of an induction machine drive with moving-horizon load torque estimator - Wallscheid, Oliver; Ngoumtsa, Etienne Florian Bouna; Böcker, Joachim (2019 IEEE International Electric Machines & Drives Conference (IEMDC))

Continuous-control-set model predictive control with integrated modulator in permanent magnet synchronous motor applications - Hanke, Sören; Wallscheid, Oliver; Böcker, Joachim (2019 IEEE International Electric Machines & Drives Conference (IEMDC))

Improved Fusion of Permanent Magnet Temperature Estimation Techniques for Synchronous Motors Using a Kalman Filter - Gaona, Daniel Efren Erazo; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Industrial Electronics)

The Role of Prices Relative to Supplemental Benefits and Service Quality in Health Plan Choice - Bünnings, Christian; Schmitz, Hendrik; Tauchmann, Harald; Ziebarth, Nicolas R. (Journal of Risk and Insurance)

Improved Knowledge Changes the Mindset: Older Adults’ Perceptions of Care Robots - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helinä; Gustafsson, Christine (HCII 2019)
This paper explores Finnish, German and Swedish older adults’ perceptions of a future welfare service with increased use of welfare technologies, specifically care robots. The issues are the rapid digitalization and development of health and welfare technology, which presently is mainly technology driven (not need or user driven), and the demographic challenge. The aim of the study was to explore older adults’ perception of the future use of welfare technology or care robots. A qualitative approach with focus group discussions was employed, followed by thematic analysis. The results are presented in four overall themes: the impact on daily life for older adults and professional caregivers, codes of practice and terms of use, dissemination of information and knowledge, and conditions for successful implementation. There were significant differences in the informants’ attitudes toward and knowledge about care robots. However, the informants’ attitudes appeared to change during the focus groups and in general, became more positive. Authentic needs, which care robots could support, refer to independence, safety and security, and the ability to manage or ease daily life or working life. The results suggest that older adults, after receiving relevant information, were open to the idea of being supported by care robots in their daily lives.
Keywords: Care robots; Older adults; Implementation; Information; Perceptions; Welfare technology

Computer-Aided Design and Optimization of an Integrated Transformer with Distributed Air Gap and Leakage Path for an LLC Resonant Converter - Keuck, Lukas; Schafmeister, Frank; Böcker, Joachim (Proc. 34th IEEE Applied Power Electronics Conference (APEC))

Computer-Aided Design and Optimization of an Integrated Transformer with Distributed Air Gap and Leakage Path for LLC Resonant Converter - Keuck, Lukas; Schafmeister, Frank; Böcker, Joachim; Jungwirth, Herbert; Schmidhuber, Michael (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Novel Current Measurement Concept for Half Bridge Topologies based on simple-to-implement Digital Current Observer - Ahmad, Mohsin Ejaz; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

LCC Resonant Converter for Piezoelectric Transducers with Phase Shift Control - Bolte, Sven; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Bidirectional Resonant Converter with Integrated Magnetics for On-Board Chargers - Bolte, Sven; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Symposium on Industrial Electronics (ISIE))

Interleaved Active Clamp Forward Converters as Single Stage On-Board DC-DC Converters for EVs – an Accurate Model and Design Considerations - Rehlaender, Philipp; Grote, Tobias; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

A PCB-Integrated Winding Using a Litz Structure for a Wireless Charging Coil - Rehlaender, Philipp; Grote, Tobias; Tikhonov, Sergey; Njiende, Hugues; Schafmeister, Frank; Böcker, Joachim; Thiemann, Peter (Proc. 21st European Conference on Power Electronics and Applications (EPE-ECCE Europe))

Analytical Topology Comparison for a Single-Stage On-Board EV-Battery Converter - Rehlaender, Philipp; Grote, Tobias; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Symposium on Industrial Electronics (ISIE))

Current measurement circuit for TCM-PFC - Pohlmann, Robert; Schafmeister, Frank

Representative Sample Extraction from Spray Flames for SMPS and HR-TEM Measurements - Tischendorf, Ricardo; Bieber, M.; Kneer, R.; Schmid, Hans-Joachim
Keywords: FSP; nanoparticle synthesis; in situ measurements